2020
DOI: 10.1002/kpm.1622
|View full text |Cite
|
Sign up to set email alerts
|

Managerial factors that influence the success of knowledge management systems: A systematic literature review

Abstract: The purpose of this research is to remove the ambiguity that clouds the analysis of knowledge management systems (KMSs). This is because of an overall lack of consensus on how KMSs adapt to the new “knowledge explosion” embraced by the booming “Big Data” hype. In this paper, a refreshing synthesis of literature will uncover benefits and identify gaps in current knowledge. These findings will also be of benefit to researchers and industries as it allows for the holistic analysis of a KMS. This systematic litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 74 publications
1
13
0
Order By: Relevance
“…The study unearthed the importance that employees attach to critical aspects of OKMSP namely, KM processes, KM effectiveness, KM culture, and KM tools. These findings are in line with the findings by Jackson et al ( 2020 ) about key factors influencing OKMSP. As the COVID‐19 pandemic forced organizations under observation to shift to WFH, the study findings are in line with the observations made by Alavi and Tiwana ( 2002 ) about virtual teams showing enhanced acceptance to KM.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The study unearthed the importance that employees attach to critical aspects of OKMSP namely, KM processes, KM effectiveness, KM culture, and KM tools. These findings are in line with the findings by Jackson et al ( 2020 ) about key factors influencing OKMSP. As the COVID‐19 pandemic forced organizations under observation to shift to WFH, the study findings are in line with the observations made by Alavi and Tiwana ( 2002 ) about virtual teams showing enhanced acceptance to KM.…”
Section: Discussionsupporting
confidence: 93%
“…Advancements in information management systems like Big Data are pushing the frontiers of KM systems. Jackson et al ( 2020 ) studied factors influencing KM system success through qualitative literature review. The study unearthed the following six distinctive aspects of managerial actions that influence the KM system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study was a continuation of our systematic literature review (Jackson et al, 2020) in which we first described a series of influential factors in KM. In brief, we searched highly ranked KM journals, compared case studies from 2014 to 2018, and found a series of six common factors that influenced the success of KM systems within an organization, which we define below.…”
Section: Primary Factors Affecting Knowledge Sharingmentioning
confidence: 92%
“…Under the ISO 30401, a KMS is not a stand-alone system, but is embedded in and supported by the organizational context. Building on the literature on knowledge management enablers (Koohang et al , 2017; Jackson et al , 2020), the standard highlights leadership and culture as the two main connectors between the KMS and the remainder of the organization. By showing commitment to the KMS, establishing a KM policy, and assigning roles and responsibilities regarding the KMS, the organization's leadership can support and direct the KMS (Section 5, ISO 30401).…”
Section: Structure and Content Of The Iso 30401 – Knowledge Managemen...mentioning
confidence: 99%
“…As evident from its title, the ISO 30401 views KM as a system. Going far beyond Alavi and Leidner's (2001) definition of Knowledge Management Systems as a set of IT tools (Jackson et al , 2020), the MSS emphasizes that all (core) knowledge-based activities of the organization must be understood as interdependent and holistic.…”
Section: Looking Back: Benchmarking the Iso 30401 Against The Literaturementioning
confidence: 99%